An Econometric Model of a Firm - Saltzman, S. (The Review of Economics and Statistics, 1967)
A LTHOUGH econometric models have been constructed for a wide variety of macro-economic systems, there have been few reports, if any, of econometric models which have attempted to examine a firm in its entirety. This paper presents some results of a study intended to develop a relatively comprehensive simultaneous-equations model of a firm. The model consists of ten relational equations and five definitional equations. Endogenous variables in the model include sales, prices, output, inventories, various cost and expense items, and investments. The effects of exogenous variables such as wage rates, raw material prices, and external demand determinants are also estimated. Other variables which would make the model more complete are considered but not included in the final version because of limitations of the available data. The data used to estimate the parameters of this quarterly model refer to a firm that is a wholly-owned division of a larger, parent corporation.' The subject firm manufactures and sells a variety of models of what is essentially one product used primarily in the manufacture of home laundry appliances such as clothes washers and dryers. The firm is in an oligopolistic market, being one of a few suppliers of this product to the home laundry equipment industry. Comparison of ordinary least squares estimates and two-stage least squares estimates of the parameters of the model indicates that for this particular sample there was not a great deal of difference in the results of these alternative estimating procedures. The two sets of estimates are generally within a few percentage points of each other and in only one case is the difference as large as 15 per cent. The inclusion of various detailed cost and expense variables in the model offers an opportunity to analyze the internal operations of this firm in some depth. However, many of the conclusions which may be drawn from this model should be considered as being extremely tentative at this time. For the firm under study, the elasticity of demand with respect to price and the elasticity of price with respect to cost are both highly inelastic. These low elasticities might be explained by the competitive nature of this particular component parts industry in which total demand is determined by factors beyond its control and where price reductions by one firm may be met by similar actions of other firms in order to eliminate any great price advantage. The fact that partial elasticity of demand is larger with respect to sales effort than to product engineering effort indicates that expenditures for sales effort are, on the average, relatively more efficient at increasing sales than expenditures for product engineering. This does not seem unreasonable, particularly in an industry where there may not be much product differentiation among firms. Also, the estimated model indicates that expenditures for product engineering, capital equipment, and administration do result in some reductions in this firm's manufacturing costs, as expected. In the original functions explaining expenditures for sales effort, capital equipment, product engineering, and manufacturing engineering, the estimates of the coefficients of certain explanatory variables such as profits, sales minus inventory, and the firm's share of the total industry sales are all negative. Although it is by no means conclusive, these negative coefficients may be interpreted as an indication that the firm is operating with satisficing [9] criteria rather than maximizing criteria with respect to sales and profits. Further analysis of these same functions explaining the expenditures for investment and expense items indicates that expenditures for capital investment and manufacturing engineering are more sensitive to changes in sales than are expendi* The author is an Assistant Professor in the Department of Industrial Engineering and Operations Research at Cornell University. He is indebted to Professor T. C. Liu for many valuable suggestions during the course of this study. The interpretation of results and any shortcomings are the author's own responsibility. 1For security reasons, the corporation will be namel ss.